Arylamidonaphtalene sulfonate compounds as a novel class of heparanase inhibitors. Issue 18 (15th September 2017) - Rondanin, Riccardo; Fochi, Sara; Baruchello, Riccardo; Bernardi, Tatiana; Oliva, Paola; Semeraro, Floriana; Simoni, Daniele; Giannini, Giuseppe
Graphical abstract: Abstract: The search for antimetastatic agents for cancer therapy may involve the ability of new compounds to maintain the tissue extracellular matrix integrity. Among known factors, heparanase, an endoglucuronidase responsible for heparan sulfate cleavage, is a promising target whose inhibition could represent a strong obstacle for metastatic cancerous mechanisms. The antimetastatic activity of some suramin derivatives reported in literature suggests a possible involvement of the heparanase enzyme. To confirm such hypothesis, we have investigated FCE27266, a molecule known for its antiangiogenic and antimetastatic properties. Other new derivatives were also synthesized and investigated. Our findings revealed that FCE27266 as well as some derivatives have a strong heparanase inhibition activity, together with no cytotoxic power. Moreover, a FCE27266 analogue (SST0546NA1;17a ) resulted also positive to lower gene expression of some proangiogenic factors.